The Effect of Full Accrual Accounting Implementation on Audit Delay (Evidence from Districts/Citied Government in Indonesia for The Years 2013-2016) - Ratu Vertiarani; Abdul Halim (The Indonesian Journal of Accounting Research, 2019)
This study investigates the effect of full accrual accounting implementation on audit delay using all districts/cities government in Indonesia for the years 2013-2016. The total sample of districts/cities government in this study are 476 cities with 4 years observation period. Using the research purposive sampling method, this study collected 1,904 samples. The independent variable in this study is the implementation of full accrual accounting, includes several control variables, such as local government size (SIZE), population and leverage. To test the hypotheseis this study used logistic regression techniques (Binary Logistics). The results of this study showed that the implementation of full accrual accounting, local government size (SIZE), population and leverage hasa significant effect on audit delay.